Akulturasi Visual dan Arsitektur Keagamaan di Kemaliq Lingsar Lombok Barat - Reza Septaria; I Nengah Bawa Atmaja; Ni Luh Gede Hadriani (Jayapangus Press, 2026)
Kemaliq Lingsar, part of the Lingsar Temple Complex in West Lombok Regency, is a sacred space born from the encounter between Balinese Hinduism and Sasak Wetu Telu Islam. Previous studies on Lingsar have largely emphasized social interaction, ritual communication, and tourism, while the visual and architectural dimensions of acculturation have received limited scholarly attention. This study aims to examine the forms of Balinese Hindu acculturation manifested in the architecture, spatial arrangement, visual symbols, and religious ritual practices of Kemaliq Lingsar, and to interpret their philosophical and social meanings. This research employed a descriptive qualitative approach with data collected through observation, visual documentation, interviews with three informants, and literature study, then analyzed using a semiotic framework of denotation and connotation. The results show that Balinese Hindu elements, such as the paduraksa (roofed) gate, guardian statues, sacred stone, holy water, and the philosophy of Tri Hita Karana, have been selectively adapted and reinterpreted within the cosmology of the Sasak Wetu Telu community without erasing local identity. Notably, the worship space still faces the qibla rather than the Balinese kaja-kelod axis, indicating that the acculturation operates on the visual and practical layers while the fundamental religious orientation remains Islamic-Sasak. Many Hindu visual elements accumulated gradually through interfaith donation and are now preserved by regulation. The study concludes that Kemaliq Lingsar represents a living model of religious harmony and cultural tolerance rooted in local wisdom.